THE EFFECT OF LIVE STREAMING AND CONTENT MARKETING FEATURES ON THE PURCHASE INTENTION OF STUDENTS OF THE FACULTY OF ECONOMICS & BUSINESS, UNIVERSITAS NEGERI MAKASSAR, CLASS OF 2023 ON THE TIKTOK SHOP APPLICATION - Fauziah Reski Aprilia; Andi Mustika Amin; Rahmat Riwayat Abadi; Andi Dewi Angreyani (Jurnal Manajemen, 2026)
Abstract: This study aims to analyze the influence of live streaming and content marketing features on the purchase intention of students of the Faculty of Economics and Business, Makassar State University, class of 2023 on the TikTok Shop application. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to respondents who are active students who use TikTok Shop. The data analysis technique was carried out using multiple linear regression analysis with the help of statistical software. The results of the study indicate that the live streaming feature has a positive and significant effect on students' purchase intention. In addition, content marketing has also been shown to have a positive and significant effect on purchase intention. Simultaneously, the live streaming and content marketing features have a significant influence on students' purchase intention on the TikTok Shop application. These findings indicate that direct interaction through live streaming and the presentation of creative, informative, and relevant content can increase students' interest and desire to make purchases. This research is expected to contribute to the development of digital marketing studies and become a practical reference for business actors in designing effective marketing strategies on social commerce platforms.Keywords: Live streaming, Content Marketing, Purchase Intention, TikTok Shop